2017
DOI: 10.1111/bcpt.12769
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Effects during and following Persistent Insulin‐Induced Hypoglycaemia in Healthy Euglycaemic Rats

Abstract: New insulin analogues with a longer duration of action and a 'peakless' pharmacokinetic profile have been developed to improve efficacy, safety and convenience for patients with diabetes. During non-clinical development, according to regulatory guidelines, these analogues are tested in healthy euglycaemic rats rendering them persistently hypoglycaemic. Little is known about the effect of persistent (24 hr/day) insulin-induced hypoglycaemia (IIH) in rats, complicating interpretation of results in pre-clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In cynomolgus monkeys, the normal serum/ plasma glucose level is about 3-4 mmol/L, 6,8,9,12 as compared to about 3.5-5 mmol/L in Göttingen minipigs, 4-6 mmol/L in Beagle dogs, 8-10 mmol/L in rats and 3.9-5.6 mmol/L in humans. [13][14][15][16][17][18] Therefore, relatively small absolute decrements in blood glucose level will correspond to a high percentage decrease; here, for instance, the fall in blood glucose level by 1.4 mM seen in the female after the first dose corresponded to a 36% decrease. In addition, the NHP was shown to have a higher basal insulin secretion, measured by C-peptide, compared to humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cynomolgus monkeys, the normal serum/ plasma glucose level is about 3-4 mmol/L, 6,8,9,12 as compared to about 3.5-5 mmol/L in Göttingen minipigs, 4-6 mmol/L in Beagle dogs, 8-10 mmol/L in rats and 3.9-5.6 mmol/L in humans. [13][14][15][16][17][18] Therefore, relatively small absolute decrements in blood glucose level will correspond to a high percentage decrease; here, for instance, the fall in blood glucose level by 1.4 mM seen in the female after the first dose corresponded to a 36% decrease. In addition, the NHP was shown to have a higher basal insulin secretion, measured by C-peptide, compared to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas rats are known to increase food intake in response to hypoglycaemia, this has to our knowledge not been documented in monkeys and it has been suggested that food intake in NHPs is not particularly responsive to excursions in blood glucose levels because they tend to eat small and variable amounts during the day and not large quantities at once. 17,20 Unfortunately, food consumption could not be assessed in the present study, as the insulin-dosed monkeys were housed with naïve animals that share food. The group housing with naïve animals as well as the group hierarchy could also have influenced food intake of the dosed animals.…”
Section: Discussionmentioning
confidence: 99%